Students’ Perspective and Experiences of Using Grammarly in Writing Thesis Backgrounds - Salsabilla, Tiara Wijayani; Maulina, Maulina; Syahriani, Ririn (Universitas Pahlawan Tuanku Tambusai, 2025)
Writing the background section of a thesis could be a challenge for final-year students, especially when it comes to using correct grammar and constructing a logical flow. Grammarly, a widely used grammar checking tool, is often relied upon to improve writing quality. This study aims to find out English Education students' perspectives and experiences of using Grammarly to help them write their thesis background. Using a descriptive qualitative method, data were collected through semi-structured interviews with six final-year students who had used the free version of Grammarly. The findings revealed that Grammarly effectively detects basic grammatical errors such as tenses, punctuation, and article usage, and increases students’ writing confidence. However, limitations include feature restrictions, dependency on internet access, and occasional inaccuracy in feedback. Students found Grammarly helpful as a preparatory tool, but acknowledged it cannot replace supervisor feedback. In conclusion, Grammarly supports grammar correction and confidence-building but should be used as a complementary, not a substitute, academic writing aid.